Fasting of Dalā'il al-Qur'ān: Text, Reception, Transmission, and Transformation - Ichwan, Mohammad Nor; Qudsy, Saifuddin Zuhri (The Faculty of Ushuluddin and Humanities, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2021)
This research aims to reveal the tradition of fasting in the Qur'an at the al-Falah Kudus Islamic Boarding School. The tradition of memorizing the Qur'an cannot be separated from the practice of fasting as a form of leisure in memorizing the Qur'an. The leisure of fasting Dalā'il al-Qur'ān at the al-Falah Islamic Boarding School is carried out when the students have completed the memorization of 30 juz. In practice, this fast must be carried out with the permission of the kyai, even though the number of days is not determined. The findings presented show that the Quran has made students who memorize the Quran memorize it, not just memorize it. The Qur'an has also encouraged them to carry out other special worship activities outside of memorizing the Qur'an. This then allows the worship activity to develop from its original form. Fasting, which was originally carried out without having anything to do with the activity of memorizing the Qur'an, was then carried out within the framework of memorizing the Qur'an. Therefore, the goal to be achieved from the fast also develops. Thus, the fasting of Dalā'il al-Qur'an has made the tradition of memorizing the Qur'an influence the development of orientation and goals to be achieved through fasting.